Mothering away from home: experiences of Zimbabwean domestic workers in South Africa - Shamase, Londeka Zamankwali; Sekaja, Lusanda (Frontiers in Sociology, 2025)
Many women leave their homes in Zimbabwe in the hopes of finding work in South Africa. In this study we investigated the experiences of Zimbabwean transnational mothers working as domestic workers in South Africa with a specific focus on how they navigate motherhood while separated from their children. We conducted semi-structured interviews to explore the visitational, financial, and emotional aspects of their separation. We used thematic analysis to interpret the data, which revealed three key themes, namely, (a) infrequent homecoming shaped by structural barriers, (b) vulnerabilities and unseen challenges of children left behind, and (c) transnational mothering. The findings highlight the emotional tax and structural constraints of mothering across borders. The study calls for a more culturally grounded understanding of parenting, specifically transnational mothering.